(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study investigated business education students rating of factor influencing career choice in universities in Edo and Delta States. The theory of this study was hinged on Krumboltz’ theory of social learning and career decision making. The descriptive survey research design was employed and the population for the study consist of 802 Business education undergraduate students from University of Benin and Delta State University. The sample size comprised 100 Business education undergraduate students selected through a proportionate sampling technique. The instrument used for data collection was structured questionnaire. The reliability of the instrument was 0.71. The data collected were analyzed using mean (࢞̅(, standard deviation and two sample independent t-test. The findings revealed that gender and students interest play a significant influence on students’ choice of business education programme. Furthermore, there is no significant difference between male and female students on their choice of option in business education in universities. It was recommended, among others, that both male and female business education students should be encouraged to enrol into business education programmes through the activities of their professional bodies and beneficiaries of the programmes.